Diversity, activity, antibiotic and heavy metal resistance of bacteria from petroleum hydrocarbon contaminated soils located in different sites - Godheja, Jai; Dixit, Krishna; Sharma, Payal (Recent Research in Science and Technology, 2014)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–> The main aim behind this project was to obtain a collection of hydrocarbonoclastic bacteria that might be suitable for bioremediation processes as soil inoculums to remove hydrocarbons in presence of heavy metals. To achieve this soils from different sites have been selected like Hindustan Petroleum of RAIPUR, BILASPUR & BACHELI strongly contaminated solely with hydrocarbons and for comparison non-contaminated soil of RAIPUR. To reveal affect of pollutants on endogenous micro biota and the bacterial shifts resulting as a consequence of different types of pollution. Different molecular biological and microbiological techniques were used. Individual samples were tested: 1. For their ability of degrading different types of hydrocarbons (aliphatic, aromatic & polycyclic aromatic hydrocarbons) 2. For their capability of resisting heavy metals (Cu2+, Zn2+, Pb2+) 3. If they proliferate in presence of antibiotics. Results that were observed was increased activity of hydro carbon clastic bacteria due to the significant Co2 production and elevated hydrocarbon degrading bacterial counts. And the bacterial communities that are diversified in number of species were influenced by the pollutants present in it was tested by the T-RFLP. Strains of highest antibiotic resistance and heavy metal tolerance were isolated from the sample. Moreover, some test indicated significant correlation between heavy metal tolerance/antibiotic resistance and antibiotic resistance/hydrocarbon degradation ability of the isolates. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>